2019
DOI: 10.1177/1545968319888642
|View full text |Cite
|
Sign up to set email alerts
|

A Stroke Recovery Trial Development Framework: Consensus-Based Core Recommendations from the Second Stroke Recovery and Rehabilitation Roundtable

Abstract: A major goal of the Stroke Recovery and Rehabilitation Roundtable (SRRR) is to accelerate development of effective treatments to enhance stroke recovery beyond that expected to occur spontaneously or with current approaches. In this paper, we describe key issues for the next generation of stroke recovery treatment trials and present the Stroke Recovery and Rehabilitation Roundtable Trials Development Framework (SRRR-TDF). An exemplar (an upper limb recovery trial) is presented to demonstrate the utility of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 41 publications
0
38
0
Order By: Relevance
“…Building up large stroke brain banks similar as we know it for neurodegenerative disorders would be a large step to be able to link findings from preclinical models to the human situation. “Better alignment of preclinical studies to clinical realities or constraints should be a priority for the field and funding bodies” as formulated by the Second Stroke Recovery and Rehabilitation Roundtable 127 may cover only one side of the medal. Even if well and thoroughly designed, preclinical and here in particular rodent models have their inherent specifics and limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Building up large stroke brain banks similar as we know it for neurodegenerative disorders would be a large step to be able to link findings from preclinical models to the human situation. “Better alignment of preclinical studies to clinical realities or constraints should be a priority for the field and funding bodies” as formulated by the Second Stroke Recovery and Rehabilitation Roundtable 127 may cover only one side of the medal. Even if well and thoroughly designed, preclinical and here in particular rodent models have their inherent specifics and limitations.…”
Section: Discussionmentioning
confidence: 99%
“…1 In humans, the interaction between treatment onset and intensity remains unclear. 2 It has been suggested that reducing daily treatment duration below 3 hours at the acute and subacute stages leads to a poorer prognosis, 3 while there may also be an upper bound beyond which high-intensity motor rehabilitation at the acute stage might lead to unwanted side effects. 4 Designing optimal rehabilitation treatment programmes for stroke patients will not be possible until we understand 'how much', 'when' and 'what' treatment should be delivered.…”
Section: Introductionmentioning
confidence: 99%
“…However, robot-assisted therapy has so far typically been applied in the context of short (frequently outpatient) therapy sessions in clinical settings (Lum et al, 2012;Page et al, 2013;Klamroth-Marganska et al, 2014), and where the presence of a supervising therapist is required to prepare and manage the complex equipment, set up the patient on/in the device and configure the appropriate therapy plan. This generates organizational and economical constraints that restrict the use of the technology (Wagner et al, 2011;Schneider et al, 2016;Rodgers et al, 2019;Ward et al, 2019) and, as a result, despite claiming high intensity (Lo et al, 2010;Rodgers et al, 2019), the therapy dose achieved using robots remains limited compared to guidelines (Bernhardt et al, 2019) and preclinical evidence (Nudo and Milliken, 1996).…”
Section: Introductionmentioning
confidence: 99%